Sea surface temperature retrieval based on simulated space-borne one-dimensional multifrequency synthetic aperture microwave radiometry - Guo, Chaogang; Ai, Weihua; Liu, Maohong; Feng, Mengyan; Qiao, Junqi; Hu, Shensen (Frontiers in Environmental Science, 2022)
The space-borne one-dimensional multifrequency synthetic aperture microwave radiometer (1D-MSAMR) offers new possibilities for detecting high spatial resolution sea surface temperature (SST). To achieve higher SST retrieval accuracy, an SST retrieval algorithm, the two-step retrieval algorithm (TSSR), is proposed based on the multiple linear regression (MLR) algorithm. In this study, we investigated the SST retrieval accuracy of 1D-MSAMR based on simulation experiments. For the study, we assumed that the frequencies of the 1D-MSAMR were 6.9, 10.65, 18.7, 23.8, and 36.5 GHz, and that all frequencies worked in a dual polarization (vertical and horizontal) manner. We used an ocean-atmosphere microwave radiation brightness temperature model and the 1D-MSAMR simulator to simulate the measured brightness temperature based on WindSat data provided by the Remote Sensing Systems (RSS). An MLR algorithm and the TSSR were then developed to retrieve the SST within the incidence angle range of 0°–65°. The results show that the SST retrieval errors of the two SST retrieval algorithms decreased with the increase of incidence angle. The TSSR had higher retrieval accuracy, especially at low incidence angle. The average retrieval accuracy of the TSSR was about 0.3 K higher than that of the MLR algorithm. The retrieval error of the TSSR was also less sensitive to the measurement error of the 6.9 GHz frequency than the MLR algorithm.